A Study on the Mechanisms of Tension-Shear Failure and the Estimation Model for Key Parameters of Free-Face-Assisted Rock Breaking - Chongmao Tang (Advances in Civil Engineering)
One huge challenge TBM construction face is to improve the breaking ability of cutters for hard rocks, making the studies on new rock breaking approaches for cutters very important. Although a lot of previous tests have proved that it is feasible to reduce the cutter force by free-face-assisted rock breaking (FM), the mechanisms behind such feasibility and the estimation methods for key parameters involved, including the maximum free face distance, crushing angle, and cutting force, remain to be studied further, limiting its applications in cutterhead design and engineering construction practice. Based on the analysis of the phenomena and laws of FM tests, this paper proposes the tensile-shear failure mechanism of FM and a piecewise linear failure criterion, which could explain the reason for the reduction of cutting force. Subsequently, a series of estimation models for the parameters above are proposed, and a series of FM tests were performed. By comparing the data obtained from the tests and calculations of the estimation model and CSM model, the estimation model in this paper is verified for its feasibility and limitations, which offered some insights on these aspects in follow-up research.